2022
DOI: 10.3389/fcell.2022.867003
|View full text |Cite
|
Sign up to set email alerts
|

NIBAN1, Exploring its Roles in Cell Survival Under Stress Context

Abstract: Cell survival must quickly activate specific mechanisms that enable to detect changes in the cellular microenvironment. The impact of these cell alteration has direct consequences on cellular homeostasis. Cellular stress, as well as its regulation and implication, has been studied in different pathologies. In this sense, the alteration in NIBAN1 expression seems to act in response to different cellular disturbances. Over the years, the knowledge of NIBAN1 functions has improved, demonstrating its important cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 72 publications
(230 reference statements)
2
8
0
Order By: Relevance
“…Our findings are in accordance with existing knowledge, as recent studies also demonstrated significant enrichment of the IFN-I pathway and innate antiviral activity following secondary BNT162b2 immunization [ 15 , 16 ]. The 18 downregulated genes were found to be biologically unlinked, implying that their differential expression has little, if any, biological significance, as these genes are mostly involved in erythrocyte functions and metabolic pathways, such as activity of alkaline phosphatase, endoplasmic reticulum stress response and endothelial cell and neutrophil migration [ 17 , 18 , 19 , 20 , 21 ]. In contrast to Arunachalam et al, we were unable to identify any correlation between the innate transcriptional signatures and adaptive immune response or age, most probably due to the small size of our cohort [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are in accordance with existing knowledge, as recent studies also demonstrated significant enrichment of the IFN-I pathway and innate antiviral activity following secondary BNT162b2 immunization [ 15 , 16 ]. The 18 downregulated genes were found to be biologically unlinked, implying that their differential expression has little, if any, biological significance, as these genes are mostly involved in erythrocyte functions and metabolic pathways, such as activity of alkaline phosphatase, endoplasmic reticulum stress response and endothelial cell and neutrophil migration [ 17 , 18 , 19 , 20 , 21 ]. In contrast to Arunachalam et al, we were unable to identify any correlation between the innate transcriptional signatures and adaptive immune response or age, most probably due to the small size of our cohort [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple genes that were affected in this resulting list have been implicated to various cancer pathologies. This includes BNIP3 63 , HIST1H4L 64 , TBX3 65 (observed in all six treatments), early growth response factor 1 (EGR1) 66 , solute carrier family 7 member 11 (SLC7A11) 65 (observed in 5 treatments) niban apoptosis regulator 1 (NIBAN1) 67 and fos proto-oncogene (FOS) 68 (observed in 3 treatments). In addition, multiple PFAS-affected genes have previously been linked to neuronal health, including MANF 69 , TXNIP 70 (impacted in all six treatments), and tolloid-like protein 2 ( TLL2) 71 (impacted in 5 treatments).…”
Section: Resultsmentioning
confidence: 99%
“…Multiple genes that were affected in this resulting list have been implicated to various pathologies. These include BNIP3 57 , HIST1H4L 58 , TBX3 59 , MANF 60 and TXNIP 61 (observed in all six treatments), early growth response factor 1 ( EGR1 ) 62 , solute carrier family 7 member 11 ( SLC7A11 ) 59 and tolloid-like protein 2 ( TLL2 ) 63 (observed in 5 treatments), niban apoptosis regulator 1 ( NIBAN1 ) 64 and fos proto-oncogene ( FOS ) 65 (observed in 3 treatments). Importantly, MANF and TXNIP have previously been implicated in neuronal health.…”
Section: Resultsmentioning
confidence: 99%
“…The NIBAN1 (niban apoptosis regulator 1) gene, also known as FAM129A , belongs to the FAM129 family (family with sequence similarity 129), which has important cellular functions in a number of diseases and carcinogenic processes. 58 NIBAN1 plays a significant role in cellular homeostasis through the regulation of cell stress and autophagy. 35 , 58 , 59 In this study, we show that phenformin treatment strongly increased the expression of DDIT4 and NIBAN1 in OSCC cells in vivo and in vitro, and importantly, the knockdown of either DDIT4 or NIBAN1 suppressed the expression of autophagic markers induced by phenformin, which suggests that phenformin induces OSCC cell autophagy dependent on DDIT4 and NIBAN1 expression.…”
Section: Discussionmentioning
confidence: 99%